Acetylation of aromatic cysteine conjugates by recombinant human N-acetyltransferase 8. (4th March 2017) - Deol, Reema; Josephy, P. David
Abstract: 1. The mercapturic acid (MA) pathway is a metabolic route for the processing of glutathione conjugates to MA ( N -acetylcysteine conjugates). An N -acetyltransferase enzyme, NAT8, catalyzes the transfer of an acetyl group from acetyl-CoA to the cysteine amino group, producing a MA, which is excreted in the urine. We expressed human NAT8 in HEK293T cells and developed an HPLC-MS method for the quantitation of the S -aryl-substituted cysteine conjugates and their MA. 2. We measured the activity of the enzyme for acetylation of benzyl-, 4-nitrobenzyl-, and 1-menaphthylcysteine substrates. 3. NAT8 catalyzed the acetylation of all three cysteine conjugates with similar Michaelis–Menten kinetics.